"Lions and wyvens and dolphins, oh my!": Jessie Mitchell Elmslie’s Arts and Crafts furniture - Hill, Marguerite (Architectural History Aotearoa, 2023)
Jessie Mitchell Elmslie was in her early twenties when she carved an intricate and highly decorative oak and kauri sideboard. The 2.5 metre high sideboard is dripping with Arts and Crafts iconography, including wyverns, lions and a Green Man with a flowing beard. Elmslie also incorporated copper tooling into her design, with beaten copper handles and repousse heraldic dolphins. Elmslie’s father, Dr Rev John Elmslie, was the minister at St Paul’s Presbyterian Church in Christchurch and one of his parishioners taught Elmslie to carve. She produced at least two large pieces of furniture during the 1890s: the sideboard now in the collection of Canterbury Museum and a walnut settle in the collection of Te Papa Tongarewa Museum of New Zealand. Woodcarving became popular with New Zealand women during the late nineteenth and early twentieth centuries. The Arts and Crafts movement, along with the establishment of art and design schools from the 1870s, meant that women were able to engage in practices formerly reserved for men. This paper will look at Elmslie and her work in the context of Arts and Crafts practice in New Zealand and consider the work of another talented carver, Evelyn Vaile.